The stability and modulation of if-then rules versus prospective planning in movement selection under dual-tasking conditions - S. E. M. Stoll; A. Wenzel; B. Hitzler; J. Randerath (Scientific Reports)
Abstract Two approaches to movement selection, if-then rules versus prospective planning, were investigated. Studies have shown that the rule-based approach leads to more efficient movement selection than the plan-based approach, though the resulting movements are the same. This dual-tasking study investigates two hypotheses explaining this discrepancy: The efficiency hypothesis states that the rule-based approach to movement selection is more efficient, and its advantage over the plan-based approach increases under any kind of enhanced task demands. The dual-mechanisms hypothesis states that the two approaches to movement selection are based on distinct mechanisms and that they can be differentially affected by secondary tasks. Forty-eight participants selected a grip in order to comfortably rotate a dowel to a target position using the rule- or the plan-based approach. Four dual-tasking conditions were added: Identifying the activity underlying an object-interaction sound, identifying and categorizing the object underlying an object-interaction sound, identifying one of four words that does not match the others semantically, and solving calculations. The rule-based approach led to more efficient movement selection in most dual-tasking conditions. However, its advantage disappeared when the secondary task was to identify and categorize objects. These results strengthen the dual-mechanisms hypothesis, and possible factors distinguishing the approaches are discussed.